2023
DOI: 10.18632/aging.204502
|View full text |Cite
|
Sign up to set email alerts
|

Immune-mediated platelet depletion augments Alzheimer’s disease neuropathological hallmarks in APP-PS1 mice

Abstract: In Alzheimer's disease (AD), platelets become dysfunctional and might contribute to amyloid beta deposition. Here, we depleted platelets in one-year-old APP Swedish PS1 dE9 (APP-PS1) transgenic mice for five days, using intraperitoneal injections of an anti-CD42b antibody, and assessed changes in cerebral amyloidosis, plaqueassociated neuritic dystrophy and gliosis. In APP-PS1 female mice, platelet depletion shifted amyloid plaque size distribution towards bigger plaques and increased neuritic dystrophy in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…To investigate whether circulating platelets modulate OPC function in vivo , we used a platelet depletion model (Figure 2A). LPC-induced focal demyelinating lesions were performed in WT mice followed by the administration of anti-CD42b at 3 dpl and every second day to prevent further platelet recruitment (Morodomi et al ., 2020; de Sousa et al ., 2023). We first confirmed that this depletion strategy leads to decreased numbers of recruited platelets, with no accumulation in the lesion (p-value < 0.05) (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether circulating platelets modulate OPC function in vivo , we used a platelet depletion model (Figure 2A). LPC-induced focal demyelinating lesions were performed in WT mice followed by the administration of anti-CD42b at 3 dpl and every second day to prevent further platelet recruitment (Morodomi et al ., 2020; de Sousa et al ., 2023). We first confirmed that this depletion strategy leads to decreased numbers of recruited platelets, with no accumulation in the lesion (p-value < 0.05) (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…In the brain, ADGRV1 is strongly expressed in neurons, but highest in astrocytes (McMillan and White, 2010) Here, we observed that deficiency of ADGRV1 leads to decreased abundance and altered morphology of astrocytes in the CA1 region of the hippocampus, most likely due to an imbalanced glutamate homeostasis. Corresponding changes in astrocyte morphology and number have been observed in diseases in which astrocytes are known to be involved in the pathogenesis such as acute brain trauma and chronic neuropathies, e.g ., Alzheimer’s disease, but also in the development of epilepsy (Wu et al, 2021; Hayashi et al, 2022; de Sousa et al, 2023). The increase in branching or convex hull area of astrocytes is thought to be a consequence of the reduced number of cells in the diseased brain due to their exploratory attempts to contact the remaining neurons.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have indicated that short‐term platelet depletion may promote amyloid plaque growth, increase the risk of neuroinflammatory dystrophy, affect microglial phagocytosis, and alter astrocyte morphology in the hippocampus of female APP‐PS1 mice. 13 , 14 The precise relationship between platelet count and the underlying molecular mechanisms regulating amyloid plaque deposition remains elusive and needs to be further investigated in future experiments.…”
Section: Discussionmentioning
confidence: 99%